Antecedents of intention to stay and the mediating effects of work-family facilitation and family satisfaction among single mother employees in Malaysia - Noraani Mustapha (2010)
Employee turnover has been a major concern among researchers in human resource development (HRD) are since it has negative impact on organization. This study was conducted to test the mediating effects of work-family facilitation and family satisfaction on the relationships between dispositional, organizational and job characteristics, and intention to stay among single mother employess. Specifically this study aimed to determine the levels of dispositional, organizational and job characteristics of 240 working single mothers in Malaysia. Besides, this study was meant to test the relationships among variables as well as the mediation effects of work-family facilitation and family satisfaction on the relationship between dispositional, organizational and job characteristics, and intention to stay. Data were collected using self-administered research questionnaire. Samples were selected through simple random sampling method whereby six out of 24 single mother associations were selected as research samples. Descriptive statistical analysis was conducted to describe the respondents. Pearson Product Moment Correlation was used to determine the relationships among variables. Structural Equation Modeling using AMOS version 16.0 was utilized for model testing and to check the precence of mediation effects in the relationships between independent and dependent variables.The Soble's z-test was used to test whether the mediators carry the effect of the independent variables on the dependent variables. The findings indicated that single mothers have levels of dispositional, organizational and job characteristics in their lives, so as their levels of work-family facilitation, family satisfaction and intention to say. There were positive significant relationships among variables except for supervisory support and job autonomy. The results also established the presence of mediation effects between the independent and dependent variables except for supervisory support and job autonomy. Organizations may utilize work-family facilitation and family satisfaction as mechanisms to promote longer retention among employees.